”Teologi Tanah Warisan”: Interpretasi 1 Raja-Raja 21:1-29 dan Relevansinya terhadap Krisis Tanah di Bali - Ni Nyoman Fransiska; Johan Johan; Gusti Ngurah Sukadana (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2026)
The conversion of customary land in Bali due to tourism expansion and the practice of nominee agreements by non-Balinese residents has threatened the sustainability of local communities’ ancestral land rights. Although the issue of customary land in Bali has been examined from the perspectives of agrarian law and sociology, a biblical study linking the narrative of 1 Kings 21 to the ancestral land crisis in Bali has never been conducted. This study addresses this gap by examining the theological significance of ancestral land in 1 Kings 21 and its relevance to contemporary customary land issues in Bali. The method employed is a historical-critical interpretation of the text of 1 Kings 21, followed by a comparative analysis of the socio-cultural context of Balinese society. The findings identify three meanings of ancestral land: (1) land as a symbol of ancestral identity, (2) land as a guarantee of generational continuity and kinship, and (3) land as the foundation of community well-being. These findings indicate that the theological framework of 1 Kings 21 can serve as a normative foundation for responding to the shift in the value of land from a sacred inheritance to an economic commodity, while also providing an ethical contribution to the advocacy of land rights for the indigenous people of Bali.